PENGARUH ORIENTASI PASAR, ORIENTASI KEWIRAUSAHAAN DAN INOVASI PRODUK TERHADAP KINERJA UMKM KERAJINAN ROTAN DI KOTA PADANG - Yentisna Yentisna; Alvin Alfian; Likanopa Syentia; Ridho Deza Perkasa (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2026)
The purpose of this study is to examine the influence of market orientation, entrepreneurial orientation, and product innovation on the performance of micro, small, and medium enterprises (MSMEs). Case study: Rattan Craft MSMEs in Padang City. This research proposal uses a saturated sampling approach, a sampling technique where all members of the population are used as samples. In this study, the sample taken is 52 business actors. The analysis technique used is multiple linear regression analysis. Based on the research results, data analysis, and discussion, 1). The entrepreneurial orientation variable has a calculated t-value of 2.661 > t-table 1.675 and a significance level of 0.011 < 0.05. Judging from these results, it can be concluded that the market orientation variable has a positive and significant influence on MSME performance. 2). Entrepreneurial orientation has a calculated t-value of 2.772 > t-table 1.675 and a significance level of 0.008 < 0.05. Based on these results, it can be concluded that the entrepreneurial orientation variable has a positive and significant influence on MSME performance. 3). Product innovation has a calculated t-value of 5.186 > 1.675, and a significance level of 0.000 < 0.05. Based on these results, it can be concluded that the product innovation variable has a positive and significant influence on MSME performance.